IMPLEMENTASI NILAI-NILAI AJARAN TAU LOTANG TERHADAP MASYARAKAT LOKAL WATTANG BACUKIKI KOTA PAREPARE - Azis, Aminah; Jufri, Muhammad (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
An important aspect that is studied from this research is at the level of implementation of Tau Lotang’s values in local community Wattang Bacukiki Kota Parepare, which has religious interpretation implication is multicultural with Islamic perspective. This research is classified as research file with qualitative research type. The approach used emphasizes case study reviews through a holistic, qualitative-descriptive model, focusing on a theological-oriented approach to theological education that emphasizes a phenomenological theological review within the normative framework. The results concluded that the form of local cultural teachings Tau Lotang in the Muslim community Wattang Bacukiki City Parepare which has been since the past and inherited until now.